Terrorist Assemblages : Homonationalism in Queer Times - Puar, Jasbir K., 1967- (Book collections on Project MUSE., 2017)
In this tenth anniversary expanded edition of Jasbir K. Puar's pathbreaking book--which features a new preface by Tavia Nyong'o and a new postscript by the author--Puar argues that configurations of sexuality, race, gender, nation, class, and ethnicity are realigning in relation to contemporary forces of securitization, counterterrorism, and nationalism.